An Assessment of Stress Status in Fattening Steers by Monitoring Heart Rate Variability: A Case of Dietary Vitamin A Restriction - Kitajima, Kaho; Oishi, Kazato; Kojima, Tomoki; Uenishi, Shogo; Yasunaka, Yudai; Sakai, Koki; Kumagai, Hajime; Hirooka, Hiroyuki (Frontiers in Animal Science, 2022)
Heart rate variability (HRV), heart beat-to-beat variations, is a measure of cardiac autonomic functions, and HRV monitoring using sensor technology can be a non-invasive way to assess stress of animals. The objective of this study was to investigate the effect of dietary vitamin A (VA) restriction to enhance beef quality on the physiological status of fattening steers by HRV analysis. Six Japanese Black steers were equally allocated into VA-restricted (RES) and VA-supplemented (SUP) groups. The RES steers were fed VA-restricted diets from 11 to 20 months of age. The inter-beat intervals and blood VA concentration were measured at 18 and 24 months of age. HRV parameters in time, frequency, and non-linear domains were calculated using the inter-beat intervals. Blood VA concentration was significantly lower in RES steers than in SUP steers at 18 months of age (P < 0.05) but did not differ between the groups at 24 months of age. The HRV analysis indicated greater sympathetic and lower parasympathetic activities in RES steers than in SUP steers (P < 0.05). However, there were significant interactions of the group and age on HRV parameters (P < 0.05), indicating that although RES steers at 18 months of age might suffer from slight stress, the response could recover to a level similar to SUP steers at 24 months of age by the increase in blood VA concentration.